ANALISIS DAYA SAING DAN DAMPAK KEBIJAKAN PEMERINTAH TERHADAP KOMODITAS TEH (STUDI KASUS: PTPN VIII AFDELING RANCABALI III) - Rahmi, Palupi Permata; Daryanto, Heny Kuswanti Suwarsinah; Winandi, Ratna (Forum Agribisnis, 2014)
Rancabali III department, National Plantation VIII produces tea with national and international standard of quality. The purpose of this study are to analyze the effect ofÂ government policies, increase of output price, increase ofÂ chemical fertilizer price, andÂ production number decline to orthodox black tea competitiveness at Rancabali III department, National Plantation VIII. The methods are Policy Analysis Matrix and sensitivity analysis. The result shows that government policies, output price, chemical fertilizer price and production number affect the competitiveness of orthodox black tea at Rancabali III department National Plantation VIII.